2021
DOI: 10.3390/s21113909
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Postural Instability in the Upright Position on Narrow Platforms and the Interactions with Postural Constraints

Abstract: Background: Loss of balance is a considerable risk factor for workers while using ladders, because they are required to maintain static postural balance on platforms of a restricted size. This study observed center of mass (CoM) and center of pressure (CoP) behaviors and evaluated the effects of the platform depth (anterior–posterior length) and working postures. Methods: Eleven male participants stood on four platforms with depths ranging from 6 to 15 cm and maintained their positions for 60 s while performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Perturbations were enacted as a pull on the trunk lasting 600 ms. During this time, the subject's COM was forcibly moved in the direction of the pull leaving them close to the boundaries of their BOS at the end of the perturbation. At this point, the COP-COM distance was minimized and thus, the ability of subjects to generate any restoring torque using the ankle strategy was minimal because the COP-COM distance is directly proportional to the restoring torque [31,32]. In the first few hundred milliseconds of the perturbation, when the COP-COM distance is maximal, we observed that subjects tried to use an ankle strategy but quickly changed to the hip strategy once the perturbation started.…”
Section: Balance Strategiesmentioning
confidence: 88%
“…Perturbations were enacted as a pull on the trunk lasting 600 ms. During this time, the subject's COM was forcibly moved in the direction of the pull leaving them close to the boundaries of their BOS at the end of the perturbation. At this point, the COP-COM distance was minimized and thus, the ability of subjects to generate any restoring torque using the ankle strategy was minimal because the COP-COM distance is directly proportional to the restoring torque [31,32]. In the first few hundred milliseconds of the perturbation, when the COP-COM distance is maximal, we observed that subjects tried to use an ankle strategy but quickly changed to the hip strategy once the perturbation started.…”
Section: Balance Strategiesmentioning
confidence: 88%
“…The one-leg standing posture is difficult to control with CoP effectively due to the narrow support surfaces on the left and right sides 26) . This may be why no In conclusion, it was shown that differences in upper body segments and mass control strategies affect CoM-TLL and CoP-Freq.…”
Section: Discussionmentioning
confidence: 99%